EKSTRAKSI INFORMASI KONTEN WEB MENGGUNAKAN PENDEKATAN BERBASIS ONTOLOGI - Susanti, Erma (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Most of information on the Internet is transmitted through unstructured information via websites. Information in the web pages usually contains main content, advertisement, navigation and other additional information. The amount of information makes it difficult to obtain the core information, value and relevant knowledge inthe form of structured information, like databases. Information extraction is a process to converting unstructured information into structured information. Applying information extraction method using ontology called Ontology-Based Information Extraction (OBIE) aims to provide semantic content for semantic web and perform extracting process using semi-automatic method (a method to minimize human intevention in extracting process). A case study to apply information extraction used â€œLonelyPlanetâ€ dataset.